Effect of Tongqiao Huoxue Decoction Combined with Western Medicine on Ischemic Stroke: A Systematic Review - Zhong, Da-yuan (Evid Based Complement Alternat Med, 2020)
OBJECTIVE: We conducted a systematic review and meta-analysis to systematically evaluate the curative effect of Tongqiao Huoxue Decoction (TQHXD) combined with Western medicine treatment (WMT) on Ischemic Stroke (IS). METHODS: Randomized controlled trials (RCTs) of TQHXD in the treatment of IS by computer retrieval of PubMed, Embase, Web of Science, Chinese Biomedical Literature Service System, CNKI, Wanfang Database, and Weipu Database. The retrieval time was taken from the establishment of the database to July 30, 2020. Two researchers, respectively, conducted a strict evaluation of the quality of the literature and extracted the data which were then entered in the RevMan5.3 software for meta-analysis. RESULTS: 40 articles were listed, which involved 3260 patients. Meta-analysis results show that TQHXD combined with WMT can significantly reduce patients' NIHSS score, serum hypersensitivity C-reactive protein (hs-CRP), plasma viscosity, serum fibrinogen, serum total cholesterol, and serum triglycerides and improve patients' ADL-Barthel scoring and treatment efficiency. However, there is no evidence that TQHXD combined with the WMT  group can significantly decrease the incidence of adverse events. CONCLUSION: The therapeutic effect of TQHXD combined with the WMT  group was significantly better than that of the WMT  alone group. For the treatment of patients with IS, TQHXD combined with WMT is worthy of application and promotion.